Thinking politically - Blondel,Jean (London, 1976)
Every subject has its amateurs and its professionals, but perhaps in politics the gaps and misunderstandings between professionals and amateurs are larger than in any other field of human inquiry. Politicians and interested observers criticize political scientists for creating too much order out of what is in reality a mixture of habits, customs and uneasy compromises; they regard students of politics as unnecessary or dangerous, harmless or wasteful. Of course, politicians, observers and the man in the street are inconsistent: they ask professionals to draft constitutions, to account for election results, to explain military coups; while governments and political groups are more frequently - too frequently for some radicals - seeking the advice of professional political scientists. But the gap is still unnecessarily wide.
Keywords: Political Science